Improving Productive Waqf in Baitul maal wa Tamwil - Zusak, M Bastomi Fahri (Jurnal Ilmiah Ekonomi Islam, 2024)
Baitul maal wa tamwil (BMT) is Islamic microfinance institutions which utilizes waqf as a nazir. This research attempts to describe the model of improving waqf productive and baitul maal of BMT. So far, the implementation of the management concepts of baitul maal and baitut tamwil has not been balanced, BMT management is too focused on commercial financing of the function of baitut tamwil. This paper used qualitative approach, based on in-depth interview with experts of waqf and BMT practitioners and academicions. The results of the study show that good management in BMT is the existence of equality or balance between maal and tamwil. Human Resources baitul maal management needs to be strengthened in improvising productive waqf. The existence of a business plan that is made will create the direction and performance of the collection and utilization of waqf assets.